2021
DOI: 10.1002/asjc.2524
|View full text |Cite
|
Sign up to set email alerts
|

Improved event‐triggered sliding mode control of switched systems with disturbances

Abstract: This paper is devoted to solving the problem of sliding mode control for discrete-time switched systems with disturbances via an improved event-triggered strategy. First, the switched sliding mode dynamics is obtained based on the pre-designed sliding mode surface. Then, on the basis of the Lyapunov functional technique and the average dwell time approach, sufficient conditions for the existence of the concerned sliding mode dynamics are established. Third, the sliding mode control law is synthesized such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…where x(k) ∈ R n is the state estimation and L 𝜎(k) ∈ R n×p is the observer gain matrix to be designed later. The error dynamic system of the observer can be obtained by subtracting (2) from the first equation in (1) and it is…”
Section: H∞ Observer Designmentioning
confidence: 99%
See 1 more Smart Citation
“…where x(k) ∈ R n is the state estimation and L 𝜎(k) ∈ R n×p is the observer gain matrix to be designed later. The error dynamic system of the observer can be obtained by subtracting (2) from the first equation in (1) and it is…”
Section: H∞ Observer Designmentioning
confidence: 99%
“…A switched system is a hybrid system composed of a series of continuous or discrete subsystems together with a switched rule that can determine the shift form among these subsystems. In view of engineering points, many practical control systems can be described by switched systems such as the intelligent robot system [1,2], electric control system [3,4], traffic system [5,6], and so on. For this reason, researches on switched systems have attracted much attention and up to now, and many excellent research results can be found in literature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Design a controller u(t) for state error system (6), which can guarantee the state of ( 6) converges to zero in the existence of unknown parameter matrices ΔA i , ΔB i , and unknown extraneous perturbation 𝑓 (t).…”
Section: Model Reference Control Objectivementioning
confidence: 99%
“…But a real system will certainly suffer form various disturbance [4], and the model parameters of itself will constantly change because of the mechanical wear and changing of external condition [5], so the built nonlinear model of a real system is not so accurate. On other words, uncertainties and perturbations are always in existence [6]. When we adopting T-S fuzzy technology to approach nonlinear model, uncertainties and unmodeled dynamics are also need to be considered, so robust control for T-S model is still an important and necessary task.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used method for dealing with stability of delayed systems is Lyapunov–Krasovskii functional method [12–14], and H$$ {H}_{\infty } $$ control is often employed to investigate dynamics of systems with disturbances. Recently, event‐triggered mechanism is widely employed in various control systems in order to save communication resources [15]. Stability analysis and controller design have been intensively investigated for switched systems with delays or/and disturbances [16, 17].…”
Section: Introductionmentioning
confidence: 99%